Linguopragmatic effectiveness of innovative methods of teaching medical English based on international experience - Mukhamedjanova, Sitorabegim Djamolitdinovna (The Lingua Spectrum, 2026)
The article elucidates the theoretical and practical significance of the linguopragmatic approach in teaching Medical English. The study analyzes the effectiveness of innovative methods, including task-based learning, simulation-based training with standardized patients and mannequins, virtual reality, corpus-driven approaches, and blended learning, in developing the pragmatic competence of medical students. Drawing on international programs, scholarly research, and best practices, the paper substantiates that integrating pragmatic training with authentic professional tasks, clinical communication scenarios, and simulations contributes significantly to the development of learners’ communicative competence. The article highlights the importance of linguopragmatic skills in such contexts as patient interaction, providing clinical recommendations, explaining diagnoses, expressing empathy, and engaging in intercultural communication. Furthermore, methodological guidelines are proposed for designing Medical English courses through the use of digital tools, corpus-based learning, and virtual environments. These recommendations aim to integrate role plays, clinical case studies, reflective tasks, and assessment criteria into the instructional process. The findings demonstrate that the linguopragmatic approach effectively enhances the professional, communicative, and intercultural adaptation of medical students, significantly improving their ability to communicate flexibly, accurately, and empathetically in international clinical settings while strengthening their overall professional training.